RARE-17. Multi-institutional craniopharyngioma cohort highlights need for more comprehensive data collection on comorbidities and quality of life. (3rd June 2022) - Marshall, Emily; Crowley, Julia; McCormack, Shana; Rood, Brian; Hankinson, Todd; Cheng, Sylvia; DeCuypere, Michael; Lam, Sandi; Goldman, Stewart; Ballester, Lance; Faig, Walter; Velasco, Ryan; et al.
Abstract: BACKGROUND: Pediatric craniopharyngioma is associated with long-term survival, but tumor- and therapy-related complications often negatively impact quality of life (QoL). Standard treatments include resection and radiation, but institutional practices vary and recurrence rates remain high. In this review, we utilized a cohort from the Children's Brain Tumor Network (CBTN) to evaluate outcomes for craniopharyngioma. METHODS: CBTN provides clinical and genomic data for pediatric patients diagnosed with primary central nervous system tumors across 25+ institutions. We collected data for 124 patients, ages 0-21, diagnosed with craniopharyngioma between 2012-2020. Variables collected included treatment, recurrence/progression, and comorbidities. RESULTS: Excluding patients without confirmed pathologic diagnosis (n=10) or follow-up data (n=39), 75 patients remained. For initial treatment, most (n=46, 61%) received surgery alone (9 partial, 33 near-total resection). Twenty-six (35%) underwent both surgery and radiation, with 9 receiving both therapies upfront and 17 receiving radiation at progression/recurrence. Four (5%) patients received chemotherapy. Over half of the cohort (n=39, 52%) had at least one progression/recurrence, and four died (5%). Significantly higher rates of progression/recurrence (84% vs. 32%, p=4.0e-5) were identified in patients that had surgery and radiation, compared to surgery alone. Time to recurrence, progression, or death was shorter for the surgery and radiation group (HR=4.1, p<1.0e-4), and for those that underwent partial versus near-total resection (HR=2.7, p=0.1.2e-2). Comorbidities were likely underreported, based on low rates of visual (32%), neuroendocrine (27%), and neurologic (28%) deficits at diagnosis, and 29 patients (39%) with unspecified medical history. CONCLUSIONS: CBTN provides a robust repository of information on treatment and survival of craniopharyngioma patients. However, we found a paucity of data on associated comorbidities and QoL outcomes. We advocate that future datasets and clinical trials routinely collect functional outcomes alongside therapy and survival data, particularly in craniopharyngioma where long-term survival is balanced with future QoL.